2017
DOI: 10.1097/prs.0000000000003154
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Workers’ Compensation on Outcome Measurement Methods after Upper Extremity Surgery: A Systematic Review and Meta-Analysis

Abstract: Background Patients who receive workers’ compensation (WC) often display worse surgical result such as prolonged pain or reduced functional ability. The outcomes of surgery can be assessed using a variety of surveys, assessments, and measurements. It is unknown if the confounding effect differs based on how results are measured. The aim of this study is to determine if these variations exist. Methods A search of full-length articles published between January 1, 1995 and December 31, 2015 was conducted using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 25 publications
3
34
1
Order By: Relevance
“…Economic Crisis and Chronic Pain has been an increasing number of meta-analysis studies exploring the consistent, statistically significant associations found between financial compensation, surgery outcomes (24,25), and long-term symptom relief and functionality (26). The meaning and significance of these findings need to be revisited in contemporary Greece, a country under financial and social strain, in which social benefits and worker compensation have shrunk dramatically.…”
Section: E541mentioning
confidence: 99%
“…Economic Crisis and Chronic Pain has been an increasing number of meta-analysis studies exploring the consistent, statistically significant associations found between financial compensation, surgery outcomes (24,25), and long-term symptom relief and functionality (26). The meaning and significance of these findings need to be revisited in contemporary Greece, a country under financial and social strain, in which social benefits and worker compensation have shrunk dramatically.…”
Section: E541mentioning
confidence: 99%
“…Most studies on workers’ compensation claims have been clinical studies about outcome of intervention, for example, surgery and how compensation claims affect outcome or recovery. 3 10 , 20 , 21 This study focused on the separate effects of a not-recognized workers’ compensation claim, and how it may affect return to work, regardless of independent disability grants from the municipality. Many studies have demonstrated that a workers’ compensation claim prolongs recovery and return to work.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is described in other studies for work-related burn injuries [11] or other orthopedic injuries [17]. This effect is described in terms of satisfaction, pain, functional measures, return to work rate, and adverse events [18].…”
Section: Methodsmentioning
confidence: 99%